Mood Investor, Cuaca, dan Pergerakan Return Pasar Saham - Wibowo, Buddi (Program Studi Akuntansi FPEB UPI, 2019)
Â Abstract. The empirical aspect of fully rational assumption in stock trading in the stock exchange is a living debate. The findings of the study that link investors' moods with the movement of stock market returns are one of the criticism of research behavioral finance towards the assumption of full rational behavior. This study aims to examine empirically the influence of weather factors on investor mood reflected in stock market returns on the Jakarta stock exchange. To test the effect of weather, this study measures extreme weather conditions both low and high state. The findings show that the temperature factor is the most significant weather factor affecting the mood of investors and driving stock returns in the Jakarta stock exchanges. Keywords. : Behavioural Finance; Mood; Stock Market Return; Weather. Abstrak. Aspek empirik dari asumsi rasionalitas penuh dalam perdagangan di bursa saham banyak digugat. Temuan penelitian yang mengkaitkan mood investor dengan pergerakan return pasar saham menjadi salah satu gugatan alur riset behavioral finance terhadap asumsi perilaku rasional penuh. Â Penelitian ini bertujuan menguji secara empirik pengaruh faktor-faktor cuaca terhadap mood investor yang tercermin pada return pasar saham di bursa saham Jakarta. Untuk menguji pengaruh cuaca, penelitian ini mengukur kondisi cuaca ekstrim baik yang rendah maupun yang tinggi. Temuan menunjukkan faktor suhu merupakan faktor cuaca yang paling signifikan mempengaruhi mood investor dan menggerakkan return saham di bursa saham Jakarta.